The subfamily Pachyotominae in Mexico (Collembola: Isotomidae) with description of a new Pachyotoma species - Palacios-Vargas, José G.; Arbea, Javier I. (Zootaxa, 2022)
Pachyotoma primamexicana sp. nov, from Popocatépetl, Mexico is described; it is similar to Pachyotoma alpa (Christiansen & Bellinger, 1980) and P. muskegis (Guthrier, 1903). It can be distinguished from all other the members of the genus by the small size of PAO (about half the size of closest eye) and the formula (2,3,3) of the slightly capitate tenent hairs. An identification key for Nearctic Pachyotominae and a table with diagnostic morphological characters to the Nearctic species of the genus with integument clearly granulated is given. Three new records of species from Mexico are listed: Pachyotoma crassicauda (Tullberg, 1871), Coloburella octogenaria (Mills & Schmidt, 1957) and Bonetrura boneti (Yosii, 1962). A discussion on the distribution of the subfamily Pachyotominae and some notes on the biogeography of the subfamily are provided.